Disease-modifying therapy in progressive multiple sclerosis: a systematic review and network meta-analysis of randomized controlled trials - Wu, Xin; Wang, Shixin; Xue, Tao; Tan, Xin; Li, Jiaxuan; Chen, Zhouqing; Wang, Zhong (Frontiers in Neurology, 2024)
Background Currently, disease-modifying therapies (DMTs) for progressive multiple sclerosis (PMS) are widely used in clinical practice. At the same time, there are a variety of drug options for DMTs, but the effect of the drugs that can better relieve symptoms and improve the prognosis are still inconclusive. Objectives This systematic review aimed to evaluate the efficacy and safety of DMTs for PMS and to identify the best among these drugs. Methods MEDLINE, EMBASE, the Cochrane Library, and clinicaltrials.gov were systematically searched to identify relevant studies published before 30 January, 2023. We assessed the certainty of the evidence using the confidence in the network meta-analysis (CINeMA) framework. We estimated the summary risk ratio (RR) for dichotomous outcomes and mean differences (MD) for continuous outcomes with 95% credible intervals (CrIs). Results We included 18 randomized controlled trials (RCTs) involving 9,234 patients in the study. DMT can effectively control the disease progression of MS. Among them, mitoxantrone, siponimod, and ocrelizumab are superior to other drug options in delaying disease progression (high certainty). Mitoxantrone was the best (with high certainty) for mitigating deterioration (progression of disability). Ocrelizumab performed best on the pre- and post-treatment Timed 25-Foot Walk test (T25FW; low certainty), as did all other agents (RR range: 1.12–1.05). In the 9-Hole Peg Test (9HPT), natalizumab performed the best (high certainty), as did all other agents (RR range: 1.59–1.09). In terms of imaging, IFN-beta-1b performed better on the new T2 hypointense lesion on contrast, before and after treatment (high certainty), while siponimod performed best on the change from baseline in the total volume of lesions on T2-weighted image contrast before and after treatment (high certainty), and sWASO had the highest area under the curve (SUCRA) value (100%). In terms of adverse events (AEs), rituximab (RR 1.01), and laquinimod (RR 1.02) were more effective than the placebo (high certainty). In terms of serious adverse events (SAEs), natalizumab (RR 1.09), and ocrelizumab (RR 1.07) were safer than placebo (high certainty). Conclusion DMTs can effectively control disease progression and reduce disease deterioration during the treatment of PMS. Systematic review registration https://inplasy.com/?s=202320071, identifier: 202320071.